Het continuüm : krant voor wie zich buiten de gender-tweedeling beweegt. (Amsterdam : Grenzeloos, 1996)
Fonds Suzan Daniel (FSD)
Periodiciteit: jaarlijks
Redactie: PB 18131, 1001 ZA Amsterdam
Nederlands
Periodiek